PEMBELAJARAN DALAM MASA PANDEMI COVID-19 - Rendy Rinaldy Saputra (Universitas Singaperbangsa Karawang, 2021)
ABSTRACT The background of conducting the research is to explore the problems faced in implementing learning activities during the Covid-19 pandemic with the aim of knowing 1) how to implement learning during the Covid-19 pandemic, and 2) what are the obstacles in implementing learning during the Covid-19 pandemic. The research was conducted with a qualitative approach by conducting a study of previous research. The data analyzed in the study were obtained through Google Scholar pages with the keyword